2014
DOI: 10.1016/j.trim.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Early posttransplant changes in circulating endothelial microparticles in patients with kidney transplantation

Abstract: Background Endothelial microparticles (EMP) are membrane vesicles shed from endothelial cell in response to injury, activation or apoptosis. Kidney transplantation (KTx) is the treatment of choice for patients with end stage kidney disease (ESKD). The aim of this study was to analyze changes in EMP and serum creatinine (SCr) in patients following KTx. Methods Blood was periodically collected from patients before (pre-KTx) and after KTx for two months. EMP were identified as CD31+/CD42b− microparticles and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 21 publications
2
38
0
Order By: Relevance
“…Again, graft losses were also associated with fibrosis/atrophy [12]. Chronic allograft injury (CAI) remains one of the main causes for allograft failure [14][15][16]. Kidney allograft rejection may ultimately cause allograft loss.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, graft losses were also associated with fibrosis/atrophy [12]. Chronic allograft injury (CAI) remains one of the main causes for allograft failure [14][15][16]. Kidney allograft rejection may ultimately cause allograft loss.…”
Section: Introductionmentioning
confidence: 99%
“…Kidney allograft rejection may ultimately cause allograft loss. Kidney allograft rejection occurs via cellular, humoral or combined mechanisms of which in many cases, the endothelium is the main target of the recipient immune system [14]. Thomas [10] identifies three types of renal transplant rejection namely, hyperacute, acute and chronic rejection or chronic allograft nephropathy (CAN).…”
Section: Introductionmentioning
confidence: 99%
“…A detailed analysis determined that most plaque EVs are of leukocyte origin, including 29% macro phage (CD14 + ), 15% lymphocyte (CD4 + ), 8% granulocyte (CD66b + ) provenience [86] . No platelet, but erythrocyte and smooth muscle cell markers were detected in EVs from the plaque lysate, recent in vitro data providing first evidence of EV generation from smooth muscle cells in healthy controls at start of the trial [48] which may reflect that these patients represent a subgroup with relatively few comorbidities. In summary, chronic elevation of endothelial EVs currently appears to be significantly associated with vascular dysfunction and atherosclerosis in renal disease.…”
Section: The Role Of Evs In Vascular Inflammation In Atherosclerosismentioning
confidence: 84%
“…Counts and provenience of circulating EVs have been characterized in patients with chronic renal impairment with and without renal replacement therapy. Some studies found elevated serum concentrations of total and CD42 + platelet EV [4446] , total, endothelial (CD31 + , CD114 + ) [43,46] , platelet (CD41 + ), and erythrocyte (CD235 + ) EVs [43] in patients with end stage renal disease, while in others, total plasma EV concentrations were unaltered [47,48] or only endothelial EVs were increased [41] . Also, the effect of the hemodialysis procedure is controversial with an increase in some [47] but not other studies [44,45] .…”
Section: Evs In Chronic Kidney Diseasementioning
confidence: 99%
See 1 more Smart Citation